PENGARUH KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN DAN KEINGINAN UNTUK MEMBELI KEMBALI DI RUMAH KULINER IBU RIO - Trisna Rosta Nova; Meylani Tuti (Human Capital Development, 2023)
This study aims to determine the effect of product quality, price perceptions on repurchase intention through satisfaction. The population in this study were buyers at Rio food stalls and by using the purposive sampling technique, a sample of 160 people was obtained. The data analysis technique used is SEM (Structural Equation Model) with the help of SmartPLS 3. The results show that all hypotheses are accepted, meaning that there is an effect of product quality on satisfaction and repurchase intention. There is also the influence of perceived price on satisfaction and repurchase intention. In addition, the results also show that there is an effect of satisfaction on repurchase intention.